The Use of Guessing Game in Teaching Speaking Descriptive Text at SMP Sunan Ampel Porong - Muhammad Nabil Makarim (PGRI Provinsi Jawa Timur, 2022)
This study was about to the implementation and the students’ responds of guessing game in teaching speaking through descriptive text at SMP Sunan Ampel Porong in the academic year 2018/2019. By applying descriptive qualitative method, the subjects of this study were the 7th grade students at SMP Sunan Ampel Porong. The data of this research were the facts written in the observation’s results and the students’ responds through the implementation of the guessing game viewed in the questionnaire items. The source of data of this research was the activity of teaching learning. The researcher was the primary instrument supported by the secondary instrument namely: observation field-note, observation checklist, and questionnaire. The result showed that the implementation of guessing game was: (1) the game activity could stimulate the students’ willingness to involve the lesson, (2) the game activity could encourage the students to speak in English and (3) the teacher was easier to control the class condition. In regard to the students’ responds, most of the students assumed that the guessing game clearly motivated them and it was fun activity. The researcher gave suggestions to 1) English teachers to conduct the class activities by providing students variation of activities, 2) students to pay more attention and more active in learning process, and 3) other researchers to explore the implementation of guessing game in other English skills.